Preparation and structure investigations metal complexes based on 2-(3-iodopyridin-2-yl)-1H-benzo[d]imidazole; Advances in synthesisand complexing; Vol. 1 : Organic Chemistry Section - Vlasenko Yu. A. Yuliya Aleksandrovna; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Shafir A. Alexandr; Postnikov P. S. Pavel Sergeevich (2019, 2019)
Title screen